WEB-BASED HEALTH SERVICES INFORMATION SYSTEM PROJECT AT INDOSEHAT CLINIC 2003 WARAKAS - Abdussalaam, Falaah; Lariska, Novembri (INFOKOM (Informatika & Komputer), 2024)
Indosehat 2003 Warakas Clinic is one of the clinics located in Tanjung Priok, there are several obstacles and problems that occur at the Indosehat 2003 clinic, one of which is that in providing health services, they still use a manual system where in making clinic reports they still use books so that they experience problems. Requires a long time in reporting, resulting in inconsistent patient data, double data, In order to meet the demands and policies and laws and regulations from various parties such as the Ministry of Health and BPJS Health, the clinic is trying to develop technology. To support better and more effective health services, it is necessary to improve by building a computerized information system so that it can provide optimal service. The research method used is descriptive method, with the system development life cycle (SDLC) approach method is a model that proposes systematic and sequential software development to describe each stage of the entire process. The SDLC model used is the waterfall model. The result of this project is an integrated health service information system that provides patient registration information, examination results, drug prescriptions and payments, making it easier in terms of reporting